Inovasi Pelayanan Publik Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Pandeglang : Studi Kasus Mal Pelayanan Publik di Pandeglang - Sifa Suryana; Leo Agustino; Arenawati Arenawati (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2021)
This Paper about public service Innovation of the investment Office and One Stop Integrated Service of Pandeglang Regency (Case Study of the Public Service Mall in Pandeglang) the purpose of the Public Service Mall This is for the realization of public services that are fast, easy, cheap, transparent by involving vertical agencies, State-Owned Enterprises / Regional-Owned Enterprises, and the private sector in one place. This study uses the theory of Rogers (in Nurdin, 2019: 30) five variables: relative advantage, compatibility, complexity, trialability, and observability. Approach The research used is a qualitative approach with a case study method. The findings of the research field concluded that the Public Service Innovation of the Investment Office and One Stop Integrated Service of Pandeglang Regency at the Public Service Mall in Pandeglang was not optimal because there were several problems such as the location of the Public Service Mall which was less strategic; the facilities and infrastructure provided are not adequate; service users are not yet fully technology literate; officers still lack discipline in punctuality of service hours, and absenteeism; and the less than optimal efforts of the Office of Investment and One Stop Services in Pandeglang Regency in socializing the Public Service Mall to the public. Keywords: Innovation, Public Service, Public Service Mall